Correlation between Antenatal Care and Anxiety in Primigravida Pregnant Women at Glagah Community Health Center - Salsabila, Hawa Nur; Sulistiawati, Sulistiawati; Jayanti, Ratna Dwi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: In the third trimester of pregnancy, the anxiety rate tends to increase, especially at the time of delivery. In addition, pregnant women who are less obedient in carrying out pregnancy tests and do not follow the integrated ANC. Therefore, pregnant women do not get information about preparation for childbirth so that when they are about to face labor, their anxiety increases. This study aims to analyze the relationship between Antenatal Care (ANC) Frequency and Anxiety in primigravida pregnant women in the third trimester at Glagah Health Center.Subjects and Method: This is a quantitative study, which is observational analytic using a cross sectional approach. The number of samples was 94 subjects who were included in the inclusion criteria with purposive sampling technique. The study was conducted in September until October 2021. The dependent variable was anxiety. The independent variables were ANC frequency, age, education, economy, family support. Data were collected using a questionnaire and analyzed by chi-square test.Results: The results showed that there was a significant relationship between frequency of ANC (p<0.001), education (p= 0.015), socioeconomy (p= 0.042), and family support (<0.001) on anxiety in third trimester primigravida pregnant women.Conclusion: Anxiety in primigravida pregnant women was influenced by frequency of ANC, education, socioeconomy, and family support.